SISTEM INFORMASI PENYEWAAN RUMAH TAMU BERBASIS WEB DI KOTA BANJARMASIN - Fitria; Priyougie; Anhar Khalid (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2022)
The development of technology is currently so fast, this is of course very influential in various aspects of people's lives that demand to get everything done quickly, precisely, easily and accurately. One of them is in terms of renting a house or inn which requires speed, convenience, accuracy and accuracy in the data processing process. Because of this, the author designed a guest house rental information system so that the guest house rental process is carried out quickly and makes it easy for prospective tenants to get information about the availability of the house to be rented without having to come directly to the place. The development of the information system uses the waterfall method to build the system and uses the HTML, PHP and MySQL database programming languages.